2015
DOI: 10.4081/gh.2015.384
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the spatial accessibility of hospital care in Sichuan Province, China

Abstract: Regional disparities in geographical access to hospital care are found throughout China. Understanding variations in the spatial accessibility of hospital care has the potential to provide decision support in healthcare planning. This study examines the hospital system in the Sichuan Province in China, which provides healthcare for more than 80 million people. We examine the impacts of accessibility characterisation via the conventional measurement approach by comparing the results to those derived using a flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
0
45
0
1
Order By: Relevance
“…The socio-economic and demographic characteristics of the two regions in Table 1 suggest that minority area is larger, has a lower GDP per capita, less urbanisation rate, fewer highway per land and much sparsely populated than the non-minority area in 2014. The average travelling time to the nearest hospital (ATH) was calculated per a shortest-path analysis method [ 21 ]. The ATH of minority counties in 2012 with a mean at 84.5 min and standard deviation (SD) at 33.6 was significant disadvantages ( p < 0.001) than that of non-minority counties (mean = 42.6, SD = 18.5).…”
Section: Resultsmentioning
confidence: 99%
“…The socio-economic and demographic characteristics of the two regions in Table 1 suggest that minority area is larger, has a lower GDP per capita, less urbanisation rate, fewer highway per land and much sparsely populated than the non-minority area in 2014. The average travelling time to the nearest hospital (ATH) was calculated per a shortest-path analysis method [ 21 ]. The ATH of minority counties in 2012 with a mean at 84.5 min and standard deviation (SD) at 33.6 was significant disadvantages ( p < 0.001) than that of non-minority counties (mean = 42.6, SD = 18.5).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that children and adolescents from non-agricultural families have regular oral hygiene habits compared with agricultural families. 24 30 The spatial accessibility in relation to the population distribution and transportation infrastructure affects access to healthcare. 22 44 …”
Section: Discussionmentioning
confidence: 99%
“… 23 The province suffers from inequalities in the level of economic development and distribution of healthcare resources. 24 The cross-sectional national survey was conducted from December 2015 to May 2016 by the Department of Preventive Dentistry, West China Hospital of Stomatology, Sichuan University. A four-stage stratified random-cluster survey sampling method was adopted to obtain a representative sample of the residents in Sichuan Province based on the number of permanent residents and non-agricultural population ratio obtained in the 2010 Sixth National Population Census.…”
Section: Methodsmentioning
confidence: 99%
“…According to China’s Statistical Yearbook of Health, nearly 60 % of outpatient and emergency treatment, and more than 70 % of inpatient treatment was provided by hospitals in 2012. Hence, differences in spatial access to hospitals represent a considerable barrier to the government’s equity goals: in 2010, 34.6 % of rural respondents to a national survey (83.87 million people) cited distance as a major barrier in getting timely hospital treatment versus only 1.37 % of urban residents [ 11 ]. Ethnic minorities are particularly vulnerable to such inequalities, since many live in remote, rural regions.…”
Section: Introductionmentioning
confidence: 99%